2011
DOI: 10.1097/mca.0b013e3283487d96
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative levels of cardiac troponin versus CK-MB and high-sensitivity C-reactive protein for the prediction of 1-year cardiovascular outcome in patients undergoing vascular surgery

Abstract: Postoperative cTnI levels seem to be superior to CK-MB and hs-CRP levels for the prediction of 1-year cardiovascular mortality and morbidity in patients undergoing elective vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Many studies have examined preoperative levels of hsCRP in a variety of non-cardiac surgical populations, 26 -28 but few have quantified the inflammatory response to non-cardiac surgery per se. 29 30 Amar and colleagues 29 reported a four-to10-fold increase in hsCRP on the first postoperative day in 195 patients undergoing thoracic non-cardiac surgery. We extend this work by showing that the change in hsCRP from baseline to the maximum value observed on the first and second postoperative days is associated with major postoperative morbidity which corroborates the findings of Amar and colleagues 29 and Kouvelos and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined preoperative levels of hsCRP in a variety of non-cardiac surgical populations, 26 -28 but few have quantified the inflammatory response to non-cardiac surgery per se. 29 30 Amar and colleagues 29 reported a four-to10-fold increase in hsCRP on the first postoperative day in 195 patients undergoing thoracic non-cardiac surgery. We extend this work by showing that the change in hsCRP from baseline to the maximum value observed on the first and second postoperative days is associated with major postoperative morbidity which corroborates the findings of Amar and colleagues 29 and Kouvelos and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…We extend this work by showing that the change in hsCRP from baseline to the maximum value observed on the first and second postoperative days is associated with major postoperative morbidity which corroborates the findings of Amar and colleagues 29 and Kouvelos and colleagues. 30 It is also well established that perioperative steroid administration blunts inflammation. 8 9 31 As might thus be expected, steroids significantly ameliorated the hsCRP response to tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, research was done in smaller cohorts of patients undergoing mainly vascular and other high-risk but elective surgical procedures, showing an incidence of postoperative myocardial injury of 8% to 52%. 4,12,13,[29][30][31][32][33][34][35][36][37][38][39] Studies with a follow-up time of 12 months found a 2-to 20-fold increased mortality risk. Studies including emergency surgery reported an incidence of 33% to 53% of postoperative myocardial injury and 4-to 12-fold increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the most likely cardioprotective intervention associated with surgery is the removal of an inflammatory focus, although this benefit won’t be realised by all patients, as a large proportion of surgical patients do not have inflammatory disease. Markers of both pre‐operative [14] and postoperative inflammation [15] have been associated with intermediate‐term morbidity or mortality, although admittedly this has been in vascular surgical patients.…”
mentioning
confidence: 99%